A Belajar Kosakata Melalui Bermain Bagi Anak Usia Dini: Learn Vocabulary Through Play for Early Childhood - Hanifah, Siti; Solehuddin, M (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2023)
This research is motivated by the problem of learning vocabulary through play activities. Vocabulary is one of the important things that need to be learned while playing in developing language development. Vocabulary learning in early childhood can have knowledge, communication skills, imagination skills, role playing and new experiences that are owned in games. This research aims to examine this research method is a Systematic Literature Review. A thorough summary in the form of a literature review regarding the role of learning while playing in increasing early childhood vocabulary. The data used in this research is secondary data. Articles were obtained from an academic database, namely Google Scholar with the keywords role of learning while playing, playing for children, vocabulary, and early childhood education. Articles reviewed within the last 10 years from 2013-2023. Based on the results of the literature review it is known that learning vocabulary through play activities can be seen from the activities or material taught by the teacher to students, the role of the teacher and students when carrying out play activities and the evaluation after learning vocabulary through playing for early childhood.